A Probabilistic Approach to Modelling Home Appliances for Demand Side Management - Çakil, Fatih; Tekdemir, Ibrahim Gürsu (Institute of Electrical and Electronics Engineers Inc., 2023)
Demand-Side Management is a set of various optimization techniques and/or strategies based on techno-economic factors which focuses on planning, implementation and monitoring in power systems. In this context, energy consumption behavior of residential users is focused on and electrical appliances are modelled in various studies in literature. Electrical energy usage patterns of residential consumers and consumption behaviors are intended to be modelled in this study. We conducted a survey for modelling electrical appliances in residential houses, findings of which form the basis for developing probabilistic models designed for demand-side management applications. After that, we applied Monte Carlo sampling method to make the statistical data and relevant probabilistic models enable a thorough probabilistic simulation. 300 virtual consumers are created by using this approach as part of the simulation and relevant outcomes are obtained finally. Besides that, a graphical user interface (GUI) is created in MATLAB to demonstrate results. It is concluded that results of the simulation carried out in this study are useful in demand side management context and they may be used for studying new dynamic price models or for testing some DSM functions in future. © 2023 IEEE.
14th International Conference on Electrical and Electronics Engineering, ELECO 2023 -- 2023-11-30 through 2023-12-02 -- Virtual, Bursa -- 197135
Keywords: Demand side management; electrical appliances; Monte Carlo Sampling method; residential energy consumption